What Explains Sovereign Debt Litigation? - Julian Schumacher; Christoph Trebesch; Henrik Enderlein (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study the occurrence of holdout litigation in the context of sovereign defaults. The number of creditor lawsuits against foreign governments has strongly increased over the past decades, but there is a large variation across crisis events. Why are some defaults followed by a “run to the courthouse” and others not? What explains the general increase in lawsuits? We address these questions based on an economic model of litigation and a new dataset capturing the near-universe of cases filed against defaulting sovereigns. We find that creditors are more likely to litigate in large debt restructurings, when governments impose high losses (“haircuts”), and when the defaulting country is more vulnerable to litigation (open economies and those with a low legal capacity). We conclude that sovereign debt lawsuits can be predicted reasonably well with a simple framework from the law and economics literature.
Keywords: F34; 330; sovereign debt; sovereign default; legal disputes; creditor lawsuits